2022
DOI: 10.1021/acs.analchem.2c04438
|View full text |Cite
|
Sign up to set email alerts
|

Novel Platinum–Nickel Composite Trap for Simultaneous and Direct Determination of Mercury and Cadmium in Soil and Its Mechanism Study

Abstract: In this work, following a metal-ceramic heater (MCH) as an electrothermal vaporizer (ETV), a novel composite Pt/Ni trap based on platinizing the foamed nickel was first fabricated to trap Hg and Cd simultaneously. So, a solid sampling Hg–Cd analyzer was developed to simultaneously detect trace Hg and Cd in soil samples, mainly consisting of an MCH, a composite Pt/Ni trap, and an atomic fluorescence spectrometer (AFS). This small-size MCH-ETV system only consumes 100 W for the complete vaporization of Hg and Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In the previous work [22], the MCH-Pt/Ni trap system worked well for precise soil analysis. However, as shown in Figure 3, when introducing a 10 mg grain sample, the peak heights of Hg and Cd without CPF were obviously lower than those with the catalytic pyrolysis furnace, presumably due to matrix interference from the grain sample, especially the presence of organic substances.…”
Section: Effect Of Etv and Catalytic Unit For Grain Samplesmentioning
confidence: 96%
See 3 more Smart Citations
“…In the previous work [22], the MCH-Pt/Ni trap system worked well for precise soil analysis. However, as shown in Figure 3, when introducing a 10 mg grain sample, the peak heights of Hg and Cd without CPF were obviously lower than those with the catalytic pyrolysis furnace, presumably due to matrix interference from the grain sample, especially the presence of organic substances.…”
Section: Effect Of Etv and Catalytic Unit For Grain Samplesmentioning
confidence: 96%
“…The preconcentration of Hg and Cd is also essential to enhance sensitivity and eliminate interference for direct sampling. Our previous study [22] has demonstrated the co-trapping and releasing of Hg and Cd by the foamed platinum-nickel wafers. Considering the redesigned ETV system and grain sample matrix, the trapping, release, and working gas conditions need to be reinvestigated in this work.…”
Section: Hg and CD Trapping And Releasing By Pt/ni Trapmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for field analysis, only sample introduction and detection are often focused on, and sample pretreatment in the field is ignored. As a result, most microplasma OES methods and devices are suitable for field analysis of environmental water samples instead of biological samples. Although direct determination of heavy metals in biological samples can be achieved by electrothermal/electromagnetic heating vaporization, the treated sample amount (0.15–20 mg) is very small, ,, leading to a higher detection limit. In addition, this method can only treat one sample at a time, greatly limiting the analytical throughput, and the high heating power makes it difficult to achieve long-term battery power, so it is still limited in field analysis.…”
mentioning
confidence: 99%